Proceedings of the Interaction Design and Children Conference 2020
DOI: 10.1145/3392063.3394403
|View full text |Cite
|
Sign up to set email alerts
|

Can design documentaries disrupt design for disability?

Abstract: This paper shows how design documentaries can motivate new perspectives for design and disability. We critically consider the ways in which design documentaries can foreground children's lived experiences and priorities, in cases where it is not always possible to involve children early on in the design process. By presenting a design case for supporting communication that involves children with severe speech and physical impairments and their social peers, we discuss how this narrative method can evoke design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, we have reported important novel findings about the practicalities, challenges, and benefits of involving people with complex speech and motor disorders who use AAC and their family members in research. Although this group is increasingly involved in the development of assistive technology and AAC devices using participatory design methodologies ( Hamidi et al, 2015 ; Ibrahim et al, 2020 ), their involvement in research is less common ( Moulam et al, 2020 ). While some individuals who use AAC are known to be lead or co-investigators in both AAC and other research fields, there is little research evaluating their experience as co-investigators or specifically focused on any barriers and facilitators to their involvement and how this affects project outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have reported important novel findings about the practicalities, challenges, and benefits of involving people with complex speech and motor disorders who use AAC and their family members in research. Although this group is increasingly involved in the development of assistive technology and AAC devices using participatory design methodologies ( Hamidi et al, 2015 ; Ibrahim et al, 2020 ), their involvement in research is less common ( Moulam et al, 2020 ). While some individuals who use AAC are known to be lead or co-investigators in both AAC and other research fields, there is little research evaluating their experience as co-investigators or specifically focused on any barriers and facilitators to their involvement and how this affects project outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2. Representing a child-centred account of communication by creating an example design documentary; which is a video story that conveys to designers detailed instances from children's lives with the intention of motivating design (see Ibrahim, Vasalou, and Clarke 2020). 3.…”
Section: Context Motivation and Goalsmentioning
confidence: 99%
“…with a linguistically oriented focus for alleviating bodily impairment. In support of this, in our prior work we identified that the majority of technology solutions for supporting communication have been informed by a restricted set of design perspectives, including the dominant, normative view that technologies alleviate bodily impairment (Ibrahim, Vasalou, and Clarke 2020).…”
Section: Introductionmentioning
confidence: 97%